PENGONTROLAN LAMPU JARAK JAUH DENGAN NODEMCU MENGGUNAKAN BLYNK - Saut P Tamba; Abdul Halim Mukti Nasution; Sri Indriani; Nida Fadhilah; Chandra Arifin (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2019)
In everyday life sometimes many people leave the lights at home alive even though they are empty. As it is known that lights are lighting devices that are very important for any activity, but often there are difficulties in controlling lights because they are still done manually, so there is often negligence in their use. Current control conditions still use the principle of controlling lights at close range. This of course results in excessive waste of electricity when traveling a considerable distance. By using a mobile home-based light control system and Blynk server, it aims to save electricity usage and make it easier to control lights from a certain distance. This system is created by using wifi technology that receives messages from clients that will be processed with the Blynk application that allows users to control home lights using Android. NodeMCU ESP8266 as a microcontroller, and the output is a relay to control the system to be on / off position. By controlling using Blynk, this tool can be operated with an Android smartphone that the majority of its users are supported by equipment that is easily available so that the house looks inhabited even though it is empty. So using the tools we make makes it easier for users to control it without having to be afraid of excessive electricity use.